Effect of S53P4 bioactive glass and low-level laser therapy on calvarial bone repair in rats submitted to zoledronic acid therapy - Bellato,Caio Peres (2021)
ABSTRACT Purpose To evaluate the influence of bioactive glass and photobiomodulation therapy (PBMT) in calvarial bone repair process in rats submitted to zoledronic acid therapy. Methods Twenty-four rats were selected and treated with the dose of 0.035 mg/kg of zoledronic acid every two weeks, totalizing eight weeks, to induce osteonecrosis. After the drug therapy, surgical procedure was performed to create 5-mm diameter parietal bone defects in the calvarial region. The rats were then randomly assigned to groups according to the following treatments: AZC: control group, treated with blood clot; AZBIO: bone defect filled with bioactive glass; AZL: treated with blood clot and submitted to PBMT; and AZBIOL: treated with bioactive glass S53P4 and submitted to PBMT. Tissue samples were collected and submitted to histomorphometric analysis after 14 and 28 days. Results At 14 days, bone neoformation in the AZBIO (52.15 ± 9.77) and AZBIOL (49.77 ± 13.58) groups presented higher values (p ≤ 0.001) compared to the AZC (23.35 ± 10.15) and AZL groups (23.32 ± 8.75). At 28 days, AZBIO (80.24 ± 5.41)still presented significant higher bone recovery values when compared to AZC (59.59 ± 16.92)and AZL (45.25 ± 5.41) groups (p = 0.048). In the 28-day period, the AZBIOL group didn’t show statistically significant difference with the other groups (71.79 ± 29.38). Conclusions The bioactive glass is an effective protocol to stimulate bone neoformation in critical defects surgically created in rats with drug induced osteonecrosis, in the studied periods of 14 and 28 days.